Diterpene chemistry—VI: SeO2/H2O2 oxidations of exocyclic olefins - Francis, M. J.; Grant, P. K.; Low, K. S.; Weavers, R. T. (Elsevier, 1976)
Unlike endocyc1ic olefins the major product from the SeO,/H,O, oxidation of exocyc1ic olefins is the same ally1ic alcohol as from the uncata1ysed oxidation. Minor products derived from epoxide intermediates were investigated. The use of SeO, as an allylic oxidant for oJefins has been extensively investigated, the functionality of the product being to a degree solvent dependent. Although the earlier mechanism of Guillemonat' is incorrect, his rules for the prediction of the position of oxidation still remain valid. A survey by Tratchenburg' of the current position in SeO, oxidation postulates allylic oxidation as proceeding through the intermediacy of an oxaselenocyclobutane to a selemte ester which IS solvated by competitive unimolecular (SN 1) and bimolecular (SN2') processes (Scheme I).